DPP-4 inhibition resembles exercise in preventing type 2 diabetes development by inhibiting hepatic protein kinase Cε expression in a mouse model of hyperinsulinemia. Issue 6 (June 2020) - Li, Yu-peng; Xiao, Jing; Liang, Xu; Pei, Yu; Han, Xiao-fei; Li, Chen-xi; Tian, Hui
Objective: Interventions for hyperinsulinemia (HINS), an early indicator of type 2 diabetes mellitus (T2DM), can significantly reduce the T2DM risk. This study aims to determine how dipeptidyl peptidase-4 (DPP-4) inhibition prevents HINS progression to T2DM through ameliorating hepatic steatosis. Methods: KKay mice were used as a HINS model and they underwent exercise or received a DPP-4 inhibitor, MK0626. Hepatic steatosis was examined and liver diacylglycerol levels were determined. Human hepatic cells (LO2) were treated with MK0626 or transfected with DPP-4 siRNA. Protein kinase C ε isoform (PKCε) and DPP-4 expression and insulin receptor substrate 1 (IRS-1) phosphorylation were assessed using immunohistochemistry and western blot. Results: KKay mice developed HINS spontaneously at 7 weeks of age. Similar to exercise, MK0626 ameliorated hepatic steatosis and reduced the liver triglyceride and diacylglycerol content. Both exercise and MK0626 suppressed diacylglycerol-induced PKCε expression and restored insulin signaling, which was shown by tyrosine phosphorylation of IRS-1, in the livers of KKay mice. Additionally, silencing DPP-4 or MK0626 treatment decreased PKCε expression in LO2 cells. Conclusions: Our data demonstrate that DPP-4 inhibition resembles exercise and effectively delays T2DM onset by suppressing hepatic PKCε expression in the HINS mouse model.